Vascular actions of oleamide in health and disease - Hopps, Jamie (2013)
Oleamide, an endocannabinoid-like mediator, is a fatty acid that shares structural similarities with anandamide. Oleamide induces cannabimimetic responses and is a potent vasodilator of rat small mesenteric arteries. The cardiovascular actions of oleamide have received relatively little attention in comparison to those of anandamide, the prototypical endocannabinoid. The aim of this study was to examine the vascular effects of oleamide in both health and disease, making a comparison with those of anandamide.